Choreographing Ireland : resistive bodies and socially engaged dance theatre - McGrath, Aoife, 1978- (Trinity College (Dublin, Ireland). Department of Drama, 2011)
This thesis provides a socio-pohtical and cuhural study of socially engaged dance theatre in the Republic of Ireland. It interrogates how the work of certain choreographers challenges the habitual primacy of the textual over the physical in Irish performance practice through the choreography of resistive dancing bodies that re-imagine narratives, subjectivities and cultural perceptions of the corporeal in Ireland. I propose that in these works, reconfigurations and disruptions of the usual positioning of bodies in social structures and nan'atives allow alternative views of society to achieve visibility, resisting the oppression of certain corporealities and challenging the hegemony of others. Extending the discussion of these choreographies to consider the cultural context out of which they emerge, and the resonance they have with specific events and specific bodies in Ireland, I also examine their connections with the "body politic" and the social choreography of bodies in everyday life. This thesis focusses primarily on the work of Michael Keegan-Dolan (Fabulous Beast Dance Theatre) and David Bolger (CoisCeim Dance Theatre), but also discusses the re-visioning of the traditional Irish step dancing body in the dance theatre of Jean Butler and Colin Dunne.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin